RETRACTED: The role of blockchain technology in advancing sustainable energy with security settlement: enhancing security and efficiency in China’s security market - Weixiong, Wang (Frontiers in Energy Research, 2023)
Blockchain technology has the potential to revolutionize securities settlement systems, offering an efficient, reliable, and cost-effective alternative to traditional methods. Its features, including distributed data authenticity, programmability, and scalability, can enhance security and efficiency in China's securities market while promoting a sustainable energy future. However, to fully leverage the benefits of blockchain in securities registration and settlement, it is crucial to address algorithmic loopholes and operational risks associated with smart contracts. Establishing blockchain technical standards and rules is also necessary to ensure smooth system operation. Furthermore, given the uncertainty of the final settlement time point, adherence to decentralization principles and the incorporation of embedded technology for supervision are essential. Legislative measures are required to regulate smart contracts and mitigate systemic risk effectively. This will ensure a stable settlement time expectation and enable fair allocation of legal responsibility among involved parties. Additionally, other regulatory approaches should be implemented to provide effective supervision and adapt to the rapid development of blockchain. By addressing challenges and risks, blockchain's full potential can be realized, enabling a sustainable energy future while enhancing security and efficiency in China's securities market.